2008
DOI: 10.3390/s8063633
|View full text |Cite
|
Sign up to set email alerts
|

Free and Forced Rossby Waves in the Western South China Sea Inferred from Jason-1 Satellite Altimetry Data

Abstract: Data from a subsurface mooring deployed in the western South China Sea shows clear intra-seasonal oscillations (ISO) at the period of 40~70 days. Analysis of remotelysensed sea surface height (SSH) anomalies in the same area indicates that these ISO signals propagate both eastward and westward. Time-longitude diagrams of ISO signals in SSH anomalies and wind-stress curl indicate that the eastward propagating SSH anomalies is forced by wind-stress curl. This is also confirmed by lag correlation between SSH anom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…The ratio of PEG to PEDOT was estimated on the basis that it requires 2.25 moles of Fe(III) to produce 1 mole of PEDOT. 38 The amount of PEG added to each oxidant solution was chosen in order to achieve films with 30%, 50% and 70% PEG contents as compared to PEDOT. For the purpose of lowering the final film thickness, the oxidant solutions were diluted with ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…The ratio of PEG to PEDOT was estimated on the basis that it requires 2.25 moles of Fe(III) to produce 1 mole of PEDOT. 38 The amount of PEG added to each oxidant solution was chosen in order to achieve films with 30%, 50% and 70% PEG contents as compared to PEDOT. For the purpose of lowering the final film thickness, the oxidant solutions were diluted with ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Oceanic Rossby and Kelvin waves certainly contribute to the intensification of oceanic circulation, but they are not interesting for us because these waves have a large wavelength (of the order of 1000 km), slow propagation (of the order of 1-10 km per day), and a period of more than 70 days (Cipollini et al, 1997;Hendon et al, 1998;Quartly et al, 2003;Wu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al [88] found that the 30-60 day intraseasonal oscillation of SST associated with the SCSWBC was under the influence of the Vietnam coastal upwelling [67,68], and this intraseasonal oscillation amplitude was obviously more significant near Vietnam coast than in any other regions. The analysis of moored buoy data found that there was also a significant period of 40-70 day intraseasonal oscillation in the subsurface near the SCSWBC region [89]. Zhuang et al [90] noted that there existed a weak seasonal signal between 100-and 200-m isobaths in the SCSWBC, which separated the strong intraseasonal signals of shallow and deep waters.…”
Section: Air-sea Interactionmentioning
confidence: 99%